Expression map of a complete set of gustatory receptor genes in chemosensory organs of Bombyx mori. (March 2017) - Guo, Huizhen; Cheng, Tingcai; Chen, Zhiwei; Jiang, Liang; Guo, Youbing; Liu, Jianqiu; Li, Shenglong; Taniai, Kiyoko; Asaoka, Kiyoshi; Kadono-Okuda, Keiko; Arunkumar, Kallare P.; Wu, Jiaqi; et al.
Abstract: Most lepidopteran species are herbivores, and interaction with host plants affects their gene expression and behavior as well as their genome evolution. Gustatory receptors (Grs) are expected to mediate host plant selection, feeding, oviposition and courtship behavior. However, due to their high diversity, sequence divergence and extremely low level of expression it has been difficult to identify precisely a complete set of Grs in Lepidoptera. By manual annotation and BAC sequencing, we improved annotation of 43 gene sequences compared with previously reported Gr s in the most studied lepidopteran model, the silkworm, Bombyx mori, and identified 7 new tandem copies of BmGr30 on chromosome 7, bringing the total number of BmGrs to 76. Among these, we mapped 68 genes to chromosomes in a newly constructed chromosome distribution map and 8 genes to scaffolds; we also found new evidence for large clusters of BmGrs, especially from the bitter receptor family. RNA-seq analysis of diverse BmGr expression patterns in chemosensory organs of larvae and adults enabled us to draw a precise organ specific map of BmGr expression. Interestingly, most of the clustered genes were expressed in the same tissues and more than half of the genes were expressed in larval maxillae, larval thoracic legs and adult legs. For example, BmGr63 showed high expression levels in all organs in both larval and adult stages. By contrast, some genes showed expression limited to specific developmental stages or organs and tissues. BmGr19 was highly expressed in larval chemosensory organs (especially antennae and thoracic legs), the single exon genes BmGr53 and BmGr67 were expressed exclusively in larval tissues, the BmGr27 – BmGr31 gene cluster on chr7 displayed a high expression level limited to adult legs and the candidate CO2 receptor BmGr2 was highly expressed in adult antennae, where few other Grs were expressed. Transcriptional analysis of the Grs in B. mori provides a valuable new reference for finding genes involved in plant-insect interactions in Lepidoptera and establishing correlations between these genes and vital insect behaviors like host plant selection and courtship for mating. Graphical abstract: Highlights: We improved annotation of 43 gustatory receptor ( Gr ) genes in Bombyx mori and identified 7 new tandem copies of BmGr30 . We constructed a new chromosome distribution map and evidenced large clusters of BmGrs on chromosome 7 and 13. We drew a precise map of BmGr expression highlighting Grs possibly involved in plant-insect interactions and courtship.